2022
DOI: 10.3390/toxics10060319
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behavior and Its Relationship with Postmortem Forensic Toxicological Findings

Abstract: Suicide affects all sociodemographic levels, age groups, and populations worldwide. The factors that can increase the risk of suicidal tendencies are widely studied. The aim of this study was to analyze the types and combinations of toxics found in fatal suicide victims with different suicide mechanisms. A total of 355 autopsies were retrospectively studied, and 26 toxics were determined and related to mechanisms of suicide. Hanging (55%), drug overdose (22.7%), and jumping from a height (17.8%) were most repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…In contrast, in high-income countries, the use of illicit drugs and medicines for suicide was more frequent. Collados-Ros et al [ 65 ] reported that most suicides were associated with drug abuse, mainly psychopharmaceuticals. In this study, the authors highlight the vital role of toxic substances in suicidal behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in high-income countries, the use of illicit drugs and medicines for suicide was more frequent. Collados-Ros et al [ 65 ] reported that most suicides were associated with drug abuse, mainly psychopharmaceuticals. In this study, the authors highlight the vital role of toxic substances in suicidal behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Collados-Ros et al [19] conducted a retrospective study in Spain from 2013 to 2018 on 355 suicide autopsy cases, of which 13% (n = 46) were suicides by poisoning. Toxico-logical investigations revealed the presence of drugs of abuse, pesticides, lorazepam, and carbon monoxide.…”
Section: Central and Southern Europementioning
confidence: 99%